If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -6 = 50x + 12 Reorder the terms: -6 + 20x = 50x + 12 Reorder the terms: -6 + 20x = 12 + 50x Solving -6 + 20x = 12 + 50x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-50x' to each side of the equation. -6 + 20x + -50x = 12 + 50x + -50x Combine like terms: 20x + -50x = -30x -6 + -30x = 12 + 50x + -50x Combine like terms: 50x + -50x = 0 -6 + -30x = 12 + 0 -6 + -30x = 12 Add '6' to each side of the equation. -6 + 6 + -30x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + -30x = 12 + 6 -30x = 12 + 6 Combine like terms: 12 + 6 = 18 -30x = 18 Divide each side by '-30'. x = -0.6 Simplifying x = -0.6
| 36-8m=8m-7m | | y+2.5=-8.5-7.6 | | -3x+21=4x | | 1320=-2x+1200 | | 1320=6x | | 5d^2-45=0 | | x^2-12x-12=0 | | 5u+4.6=10.6 | | -5y-1(5y-9)=1+2(8-y) | | 6(x+9)+2=-8(x-7)-9 | | 5(5y+4)-17=6(3y-3)-7 | | 4(3x+21)=24 | | 5x+1=4(x+5)+9 | | 8(x-11)-6=20x-190 | | 20+-25= | | -2(9n+4)=22-7n | | h^2-3h+c=0 | | 4m^2+2n=3 | | 6x+8-13x+10=x+6+x+3x | | -5g=g-h | | 2(3c-1)-4=4c+8 | | (3d+6)(4d-11)=0 | | 10x+3x-4= | | 12x-3x+6x+5x= | | 2x(x+5)=870 | | 5y=4y^2-6 | | 2x^2-20x-44=0 | | 6c^2-11c+3=0 | | x^5-789=0 | | 2x+3x-3+10=4x+14 | | 6x+6=-112-10x | | 12x^4+12x^3-9x^2+16x-4=0 |